Avascular necrosis of the right femoral head in female patient with Systemic Lupus Erythematosus - A Sinaga; H Nufus; Bambang Setiyohadi (Indonesian Journal of Rheumatology, 2014)
Avascular necrosis (also known as osteonecrosis, aseptic necrosis, or ischemic necrosis) represents collection of pathologic conditions from various etiologies causing impairment of blood supply to particular bone resulting in bone cellular death.Avascular necrosis remains a significant cause of morbidity in patients with systemic lupus erythematosus (SLE).1 It often involves multiple joints in SLE, in which the femoral head is involvedin most of these patients. Corticosteroids use is known as a major risk factor in the development of this complication.2-3 We report this case due to its quite common occurrence in SLE patients. The early recognition of avascular necrosis is essentialto prevent morbidity